2015
DOI: 10.1093/nar/gkv587
|View full text |Cite|
|
Sign up to set email alerts
|

Sequence-independent characterization of viruses based on the pattern of viral small RNAs produced by the host

Abstract: Virus surveillance in vector insects is potentially of great benefit to public health. Large-scale sequencing of small and long RNAs has previously been used to detect viruses, but without any formal comparison of different strategies. Furthermore, the identification of viral sequences largely depends on similarity searches against reference databases. Here, we developed a sequence-independent strategy based on virus-derived small RNAs produced by the host response, such as the RNA interference pathway. In ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
136
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(148 citation statements)
references
References 63 publications
4
136
1
Order By: Relevance
“…Both insects and plants use RNAi as a primary defense against virus infections. RNAi activity results in distinct populations of overlapping sRNAs derived from the RNAi-targeted viral genomes, and in insects, 21-nt sRNAs represent the primary size class (9,60,61,(96)(97)(98). In our study, the size distribution of sRNAs mapping to the putative viruses had a prominent peak at 21 nt (data not shown), suggesting that these putative viruses may originate from viral infections of D. citri and may be processed by the antiviral RNAi machinery.…”
Section: Discussionmentioning
confidence: 54%
“…Both insects and plants use RNAi as a primary defense against virus infections. RNAi activity results in distinct populations of overlapping sRNAs derived from the RNAi-targeted viral genomes, and in insects, 21-nt sRNAs represent the primary size class (9,60,61,(96)(97)(98). In our study, the size distribution of sRNAs mapping to the putative viruses had a prominent peak at 21 nt (data not shown), suggesting that these putative viruses may originate from viral infections of D. citri and may be processed by the antiviral RNAi machinery.…”
Section: Discussionmentioning
confidence: 54%
“…E xperiments in the model organism Drosophila melanogaster have shown that RNA interference (RNAi) plays a major role in antiviral immunity in insects: (i) flies with mutations for the three key genes of the small interfering RNA (siRNA) pathway, Dicer-2, Argonaute 2, and r2d2, show increased sensitivity to infection by RNA and DNA viruses (1-6); (ii) Dicer-2-dependent 21-nucleotide siRNAs of viral origin accumulate in virus-infected flies (1,3,4,(7)(8)(9); (iii) several insect viruses express viral suppressors of RNAi (5,(10)(11)(12). The importance of this pathway in the control of viral infections has been confirmed in other insects, in particular, the vector mosquito genera Aedes and Culex, which transmit important human pathogens such as dengue virus, West Nile virus, and other arthropod-borne viruses (13)(14)(15)(16)(17)(18).…”
Section: Importancementioning
confidence: 99%
“…2). Thus our results strongly suggest that these Culex mosquitoes were devoid of actively replicating exogenous viruses and do not induce RNAibased antiviral responses.To assess the presence of other viruses, metagenomic analysis of small RNA libraries was performed [55]. Briefly, small RNA libraries were submitted to quality control, adaptors were removed and the libraries filtered to remove reads containing ambiguous nucleotides.…”
mentioning
confidence: 99%